Bridging the gap between the science of cultured meat and public perceptions. (October 2020) - Tomiyama, A. Janet; Kawecki, N. Stephanie; Rosenfeld, Daniel L.; Jay, Jennifer A.; Rajagopal, Deepak; Rowat, Amy C.
Abstract: Background: The environmental impact of meat consumption requires immediate action. Cultured meat—which is emerging through technologies to grow meat ex vivo—has exciting potential to offset the burden of livestock agriculture by providing an alternative method to sustainably produce meat without requiring individuals to become vegetarian. However, consumer uptake of cultured meat may be challenged by negative public perceptions. Scope and approach: In this Review, we assert that the academic sector can play a vital role by understanding and communicating the science of cultured meat to the public. We discuss how crosstalk between the science and technology of cultured meat and the behavioral sciences will be critical to overcome challenges in public perceptions, and ultimately to realize the environmental benefits of cultured meat. We identify research and outreach priorities for the academic sector as well as potential policy actions to achieve the maximum benefits of cultured meat for planetary health. Highlights: Cultured meat has potential to reduce the environmental impact of what we eat. Although cultured meat is not yet on the market, public opinions are already forming. Cultured meat science can increase acceptability by improving flavor and texture. Behavioral science can increase acceptability by identifying modifiable perceptions. Academics should transparently communicate the science of cultured meat to the public.